Tinjauan Hukum Atas Frasa “Tanpa Persetujuan” Pada Permendikbudristek Nomor 30 Tahun 2021 Terkait Tindak Seksual di Lingkungan Perguruan Tinggi - Sylvani; Winsherly Tan (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Sexual violence on college campuses has become an urgency, initiated by various parties, especially students. In response to this, the Minister of Education of Indonesia issued, Regulation of the Minister of Education, Culture, Research, and Technology Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education. However, some people appear to have repudiation towards the regulation, concerning the phrase